Characteristics of indicators of bioelectric activity of muscles in the implementation of motor actions of athletes who have completed their careers - E.N. Chernysheva,; E.N. Karaseva,; E.B. Kartashova, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the parameters of the activity of the neuromuscular apparatus during the performance of various technical elements by athletes who have completed their careers. Methods and structure of the study. The scientific experiment was carried out in the laboratory of neurophysiology (Scientific Research Institute of Problems of Sports and health-improving physical Culture, Velikiye Luki) with the participation of a male contingent with many years of experience in competitive activity in speed-strength sports in the past. Qualification - Master of Sports and Master of Sports of International Class. The registration of muscle activity parameters was carried out using modern automated equipment when performing special motor actions and was evaluated by the following criteria: frequency, amplitude, integral. Processing of the results of the study was carried out with a special computer program MegaWin. Results and conclusions. In the course of the experiment, objective information was obtained on the parameters of the activity of the neuromuscular apparatus during the performance of technical elements of varying coordination complexity. The results of the study allowed us to draw the following conclusions: in game activities, when performing technical elements, the main work is performed by 70.5-75.2% of active skeletal muscles. The mechanisms for regulating the activity of the muscles that receive the main movement have specific features, taking into account the type of activity and are an argument for scientific support for the organization of a motor regimen of a health-improving orientation for athletes who have completed their careers in elite sports.